The Relationship between Left Ventricular Ejection Fraction (EF) and Depression Status, psychopathological status and coping mechanism in Heart Failure Patients: A Cross-Sectional Study in Malang, Indonesia - Astrid Pramudya; M. Rizki Fadlan; Yusuf Arifin; M. Saifur Rohman (Publikasi Indonesia, 2025)
This cross-sectional study examined the relationship between Left Ventricular Ejection Fraction (LVEF) and depression status, psychopathological symptoms, and coping mechanisms among 342 heart failure (HF) patients treated at Saiful Anwar General Hospital, Malang. Depression and anxiety were measured using the Montgomery–Åsberg Depression Rating Scale (MADRS), while coping mechanisms were categorized into problem-focused, emotion-focused, cognitive-focused, and maladaptive styles. The prevalence of depression was 42.4%, and anxiety was 52.6%, indicating a substantial psychological burden in this population. Bivariate analysis showed no significant difference in mean LVEF between depressed and non-depressed patients, suggesting that LVEF is not an independent predictor of depression. In contrast, NYHA Functional Class demonstrated a strong and significant association with depression, with higher classes indicating increased risk. Maladaptive coping emerged as the most common coping strategy (48.3%), particularly among individuals with low socioeconomic and educational levels, who also exhibited significantly higher rates of depression and anxiety. These findings highlight that subjective functional limitations and psychosocial vulnerabilities have greater influence on depression than objective cardiac function. The study underscores the importance of integrating routine psychological screening, coping-skills interventions, and tailored psychosocial support into HF management to improve patient outcomes.